Virtual chromoendoscopy improves the diagnostic yield of small bowel capsule endoscopy in obscure gastrointestinal bleeding - Carvalho, Pedro Boal (2016)
Background: Small bowel capsule endoscopy represents the initial investigation for obscure gastrointestinal bleeding. Flexible spectral imaging colour enhancement (FICE) is a virtual chromoendoscopy technique designed to enhance mucosal lesions, available in different settings according to light wave-length - FICE1, 2 and 3. Aims: To compare the diagnostic yield of FICE1 and white light during capsule endoscopy in patients with obscure gastrointestinal bleeding. Methods: Retrospective single-centre study including 60 consecutive patients referred for small bowel capsule endoscopy for obscure gastrointestinal bleeding. Endoscopies were independently reviewed in FICE1 and white light; findings were then reviewed by another researcher, establishing a gold standard. Diagnostic yield was defined as the presence of lesions with high bleeding potential (P2) angioectasias, ulcers or tumours. Results: Diagnostic yield using FICE1 was significantly higher than white light (55% vs 42%, p = 0.021). A superior number of P2 lesions was detected with FICE1 (74 vs 44, p = 0.003), particularly angioectasias (54 vs 26, p = 0.002), but not ulcers or tumours. Conclusions: FICE1 was significantly superior to white light, resulting in a 13% improvement in diagnostic yield, and potentially bleeding lesions particularly angioectasias were more often observed. Our results support the use of FICE1 while reviewing small bowel capsule endoscopy for obscure gastrointestinal bleeding.